Intralymphatic GAD-alum Injection Modulates B Cell Response and Induces Follicular Helper T Cells and PD-1+ CD8+ T Cells in Patients With Recent-Onset Type 1 Diabetes - Barcenilla, Hugo; Pihl, Mikael; Wahlberg, Jeanette; Ludvigsson, Johnny; Casas, Rosaura (Frontiers in Immunology, 2022)
Antigen-specific immunotherapy is an appealing strategy to preserve beta-cell function in type 1 diabetes, although the approach has yet to meet its therapeutic endpoint. Direct administration of autoantigen into lymph nodes has emerged as an alternative administration route that can improve the efficacy of the treatment. In the first open-label clinical trial in humans, injection of aluminum-formulated glutamic acid decarboxylase (GAD-alum) into an inguinal lymph node led to the promising preservation of C-peptide in patients with recent-onset type 1 diabetes. The treatment induced a distinct immunomodulatory effect, but the response at the cell level has not been fully characterized. Here we used mass cytometry to profile the immune landscape in peripheral blood mononuclear cells from 12 participants of the study before and after 15 months of treatment. The immunomodulatory effect of the therapy included reduction of naïve and unswitched memory B cells, increase in follicular helper T cells, and expansion of PD-1+ CD69+ cells in both CD8+ and double negative T cells. In vitro stimulation with GAD65 only affected effector CD8+ T cells in samples collected before the treatment. However, the recall response to antigen after 15 months included induction of CXCR3+ and CD11c+Tbet+ B cells, PD-1high follicular helper T cells and exhausted-like CD8+ T cells. This study provides a deeper insight into the immunological changes associated with GAD-alum administration directly into the lymph nodes.